Pharmacological studies on the laxative effects of Fagonia indica on rodents (Bangladesh Journal of Pharmacology, 2019)
This study explores the pharmacological basis for the folk use of Fagonia indica in constipation using in vivo and in vitro assays. The crude extract of F. indica contained tannins, saponins, anthraquinones, alkaloids, flavonoids, glycosides and phenols. The administration of F. indica extract (100 and 300 mg/kg) to mice caused a partially atropine-sensitive 35 and 42.6% laxation, respectively, similar to ursolic acid which showed 22 and 36% laxation at 10 and 30 mg/kg, respectively. In loperamide-induced constipation mice, F. indica (27.3 and 34.6%) and ursolic acid (15 and 28%) also displayed laxative effects at the aforementioned doses. In mice and rats ileum, F. indica, its fractions (ethyl acetate, aqueous) and ursolic acid produced atropine-sensitive stimulatory effects, while in rats ileum, F. indica and aqueous fraction showed partially atropine-sensitive effects. F. indica and ursolic acid possess laxative and species-specific gut stimulant effects predominantly involving the activation of muscarinic receptor, thus eliciting its folk use in constipation.Video Clip of Methodology:7 min 7 sec:  Click to watch